2006
DOI: 10.1128/jvi.80.10.4656-4663.2006
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the Bovine Spongiform Encephalopathy-Specific Prion Protein by Dendritic Cells

Abstract: Dendritic cells (DC) are suspected to be involved in transmissible spongiform encephalopathies, including bovine spongiform encephalopathy (BSE). We detected the disease-specific, protease-resistant prion protein (PrP bse ) in splenic DC purified by magnetic cell sorting 45 days after intraperitoneal inoculation of BSE prions in immunocompetent mice. We showed that bone marrow-derived DC (BMDC) from wild-type or PrP-null mice acquired both PrP bse and prion infectivity within 2 h of in vitro culture with a BSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…2 and 5 (14,(30)(31)(32)(33)(34), and PrP Sc in scrapie-infected cells can be degraded by cocultivation with dendritic cells (35,36). Our data demonstrate that cells disaggregate PrP Sc within the first 24 h following infection with scrapie.…”
Section: Smaller Prpmentioning
confidence: 60%
“…2 and 5 (14,(30)(31)(32)(33)(34), and PrP Sc in scrapie-infected cells can be degraded by cocultivation with dendritic cells (35,36). Our data demonstrate that cells disaggregate PrP Sc within the first 24 h following infection with scrapie.…”
Section: Smaller Prpmentioning
confidence: 60%
“…Indeed, DCs were shown to transport prions to the mesenteric lymph after oral inoculation (26), and to transfer prion infection to the brain (27). Other studies suggest that DCs can degrade TSE agents (28,29), as do macrophages (30).…”
Section: Prion Protein Expression By Mouse Dendritic Cells Ismentioning
confidence: 99%
“…The role of DCs in prion disease appears to be ambiguous. Some authors have shown, through in vitro models, that DCs can impair prion dissemination and that they are able to process PrP Sc , by cysteine protease, and to decrease the amount of infectivity associated with scrapie (Luhr et al 2002(Luhr et al , 2004 or BSE (Rybner-Barnier et al 2006). Several studies have demonstrated that DCs act in the spreading of prions.…”
Section: Introductionmentioning
confidence: 99%